1990
DOI: 10.1038/eye.1990.99
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of ophthalmic problems in the contact lens wearing population

Abstract: In a prospective study all contact lens wearers presenting to the ophthalmic casualty department of the University Hospital Nottingham within a six month period were examined to determine the number and pattern of ophthalmic problems occurring in this group. This information was then compared with prescribing information from contact lens dispensers in the city. The incidence of problems associated with contact lens wear within the first six months of starting to use a new contact lens was found to be 0.9% for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Novel case designs to reduce microbial contamination are being studied . Contact lenses handled inappropriately can adversely affect most anterior ocular structures . The most frequent complications based on the eye site are summarized in Table 10 .…”
Section: Contamination In Contact Lensesmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel case designs to reduce microbial contamination are being studied . Contact lenses handled inappropriately can adversely affect most anterior ocular structures . The most frequent complications based on the eye site are summarized in Table 10 .…”
Section: Contamination In Contact Lensesmentioning
confidence: 99%
“…Contact lenses were used as smart delivery systems to achieve extended drug releasing times, and as wearable biosensing platforms . On the other hand, contact lens wear was found to induce adverse effects, the most frequent being discomfort, microbial keratitis, allergies and corneal complications …”
Section: Introductionmentioning
confidence: 99%
“…44,[49][50][51] Although contact lenses offer convenience to users, there are disadvantages to their use. 59 One common complaint with contact lens use is a feeling of discomfort. 60 Other adverse effects include allergic reactions, microbial keratitis, and corneal inflammation.…”
Section: Advances In Contact Lens Sensorsmentioning
confidence: 99%
“…Contact lens solutions contaminated with Serratia marcescens have been associated with corneal ulcers (Bernstein & Maddox 1973;Benson 1976;Cooper & Constable 1977;Reinhardt et al 1979, Parment & Ronnerstam 1981Penley et al 1981;Mayo et al 1987;Lea et al 1990;Sanders et al 1990, Wilson et al 1990). Penley et al (1981) had suggested that S. marcescens should be used as a prime challenge organism for evaluating chemical disinfection systems for contact lenses.…”
Section: The Ability Of Serratia Marcescens To Survive In Solutions Fmentioning
confidence: 99%